"Does anyone even notice us?" COVID-19’s impact on academics’ well-being in a developing country - Hardman, J.; Watermeyer, R.; Shankar, K.; Ratnadeep Suri, V.; Crick, T.; Knight, K.; McGaughey, F.; Chung, R. (South African Journal of Higher Education, 2022)
In March 2020, the President of South African announced that the nation would go into full lockdown in the wake of an increase in COVID-19 infections. Academics had, in some instances, only one day to prepare for “emergency remote teaching”. Few academics had taught online before, as South Africa’s internet connectivity is not guaranteed in underprivileged areas, where 80 per cent of the population reside. The online move thus necessitated an entirely novel pedagogy for most academics, with high potential for an escalation of work-related stress and related illness, outcomes we have related in the wider sphere of workplace readjustment during COVID-19, to a state of “pandemia”. In this article, we report on an institutional case study where we surveyed n=136 academics from a university in the Western Cape, South Africa to learn more about impacts of COVID-19 on their work. The data analysis adopts Ryff’s (1995) theory of well-being. Findings indicate that the enforced lockdown due to COVID-19 and the subsequent move to online teaching has had a negative impact on academics’ sense of well-being. However, the emergence of positive, caring relationships between colleagues is reported as a significant outcome of the COVID-19 enforced move to online teaching.